Cell polarity signalling at the birth of multicellularity: What can we learn from the first animals - Wright, Bree A.; Kvansakul, Marc; Schierwater, Bernd; Humbert, Patrick O. (Frontiers in Cell and Developmental Biology, 2022)
The innovation of multicellularity has driven the unparalleled evolution of animals (Metazoa). 20 But how is a multicellular organism formed and how is its architecture maintained faithfully? 21 The defining properties and rules required for the establishment of the architecture of 22 multicellular organisms include the development of adhesive cell interactions, orientation of 23 division axis, and the ability to reposition daughter cells over long distances. Central to all 24 these properties is the ability to generate asymmetry (polarity), coordinated by a highly 25 conserved set of proteins known as cell polarity regulators. The cell polarity complexes, 26 Scribble, Par and Crumbs, are considered to be a metazoan innovation with apicobasal 27 polarity and adherens junctions both believed to be present in all animals. A better 28 understanding of the fundamental mechanisms regulating cell polarity and tissue 29 architecture should provide key insights into the development and regeneration of all animals 30 including humans. Here we review what is currently known about cell polarity and its control 31 in the most basal metazoans, and how these first examples of multicellular life can inform us 32 about the core mechanisms of tissue organisation and repair, and ultimately diseases of 33 tissue organisation, such as cancer.